Fatigue and psychosocial factors associated with self-concept in pediatric cancer patients - Pratiwi, Pramudita Hening; Hapsari, Happy Indri; Puji Utami, Ratih Dwilestari (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Childhood cancer is a chronic disease that requires intensive treatment, such as chemotherapy and radiotherapy. While effective, these treatments often cause various side effects, with fatigue being one of the most common complaints. Fatigue not only impacts the physical health but also significantly impairs the activities, social interactions, and self-concept of children with cancer. Purpose: This study aimed to analyze the factors that influence the self-concept of children with cancer undergoing treatment at Dr. Moewardi Surakarta Regional Hospital. Method: This study used a cross-sectional design. It was conducted at Dr. Moewardi Hospital Surakarta in March 2025, involving 90 children with cancer aged 8-18 years old, selected using consecutive sampling from a population of 907 children with cancer. The research instruments used a demographic data questionnaire, the PedsQL multidimensional fatigue scale (MFS), and the self-perception profile for children (SPPC). Data were analyzed using multiple linear regression. Results: The results of this study that fatigue is the most significant and consistent predictor of various dimensions of children's self-concept, even influencing nearly all subscales measured, including academic competence, athletic competence, physical appearance, and global self-esteem. Regression analysis corroborates this finding by showing that behavioral self-concept is significantly influenced by educational status and fatigue (p<0.001, R2 =0.165), while global self-esteem is influenced by type of care and fatigue (p<0.001, R2 =0.194). Although other factors such as educational status and gender are also associated with certain dimensions, fatigue is the only factor that universally and comprehensively influences nearly every aspect of children's self-concept. Conclusions: Fatigue, child's educational status, gender, and type of treatment influence the self-concept of children with cancer.